Impactos econômicos, tecnológicos e sociais do desenvolvimento das pessoas na TV Amazonas, pela Fundação Rede Amazônica - a percepção de diretores, gerentes e funcionários - Costa, Mario de Silva (2001)
This research has the objective to present the economic, technological and social impacts on the TV Amazonas' employees development. The study was made based on the perception of directors, managers and old employees of the organization, since the creation of the Rede Amazonica Foundation. The methodical procedures were based on the phenomenologic-hermeneutic approach, using theoretical study, text analysis, documents and interviews. The theoretical referential was based on publications about the history of the television in the world, Brazil and Amazon. It looked at digital television, the importance of the education on people's development and the society, as a whole changes in the labor market, professional qualification; professional education and social responsibility. The results show that employees qualification has contributed directly to the economic, technological and social growth of TV Amazonas.